Oldest record of Thinocoridae (Aves, Charadriiformes) from South America - Agnolin, Federico (2016)
Here we describe an isolated distal end of tarsometatarsus coming from the late Miocene levels of the Loma de Las Tapias Formation (San Juan Province, Argentina). The specimen was identified as a Thinocoridae, and constitutes the oldest record for the clade. It also represents the only Tertiary finding for the family from South America and one of the scarce avian remains reported from central Argentina. This record provides new information on the palaeobiogeography of the clade.